The FY2010-FY2012 Medium-Term Administrative, Restructuring, and Capital Budgets. (Policy Papers; Policy Paper, 2009)
This paper presents for Executive Board approval proposals for the FY 10-12 medium-term administrative budget, and the FY 10 capital budget in the context of the FY 10-12 capital plan. It also proposes to carry forward up to six percent of the unspent resources from the FY 09 administrative budget to help finance increased costs associated with the global financial crisis.